SOCIAL ACTORS AND COMMERCIAL CIRCUITS FOR THE SUPPLY OF MEAT IN THE CITY OF BUENOS AIRES (1750-1760) - Pelozatto Reilly, Mauro Luis (2023)
This article aims to make and present a qualitative analysis of the main suppliers (breeders, Matanzas, intermediaries, merchants, etc.), and their participation in the circuits of production, circulation and marketing of livestock products related to the supply of the City of Buenos Aires (live cattle, meat, leathers, tallow and fat). Undestanding the latter as one of the main markets at the local level, we consider a period characterized by a trend towards political changes, demographic growth and demand for food in Buenos Aires, and it is based on the idea that the Council functioned as the most prominent representative and intervening body to guarantee urban supply. The chronological cut is strictly due to the changes in the regulated mechanisms that were promoted to ensure supplies of provisions of beef origin: the transition from the public auction (Obligation) to the slaughterhouse organized in sites managed by individuals (‘‘heads of corrals’’), passing through the controls of the licenses requested by the ‘‘neighbor breeders’’ to collect from raised herds, slaughter of leathers and extraction of tallow and fat. To comply with what was proposed, data extracted from the Chapter Agreements, and from various files from the Archive of the City Council itself, were systematized, which allow us to appreciate the nature of municipal policies, and the descriptions they provide about the actors involved, theis businesses and commercial practices.